1993
DOI: 10.1016/0014-5793(93)81213-j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metabotropic glutamate receptors coupled to a pertussis toxin sensitive G‐protein in bovine brain coated vesicles

Abstract: Glutamate metabotropic receptors (mGluRs) in bovine brain coated vesicles have been characterized by pharmacological and kinetic binding experiments. Saturation experiments revealed a single binding site with a Kd = 607.9 f 78.5 nM and a B,,,,, = 6.45 f 0.88 pmol/mg protein. The specific binding of Lj3H]glutamate to mGluRs is regulated by guanine nucleotides. Guanosine-5'-triphosphate (GTP; 100 PM) shifts the agonist competition curves to the right, increasing the XC, values. Pertussis toxin treatment produces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…1S,3R-ACPD-sensitive [3H]glutamate binding has been reported by others using clathrin-coated bovine brain vesicles (Martin et al, 1991(Martin et al, , 1993 and in rat brain sections by using autoradiographic imaging (Cha et al, 1990;Greenamyre et al, 1990;Catania et al, 1993). Although the assay conditions were somewhat different, it is probable that [3H]glutamate binding to the QUIS-sensitive sites studied here corresponds to the AMPA-insensitive, QUIS-sensitive, [3H]glutamate binding reported by Cha et al .…”
Section: Fig 2 Effect Of Anions On 1s3r-acpdsupporting
confidence: 58%
“…1S,3R-ACPD-sensitive [3H]glutamate binding has been reported by others using clathrin-coated bovine brain vesicles (Martin et al, 1991(Martin et al, , 1993 and in rat brain sections by using autoradiographic imaging (Cha et al, 1990;Greenamyre et al, 1990;Catania et al, 1993). Although the assay conditions were somewhat different, it is probable that [3H]glutamate binding to the QUIS-sensitive sites studied here corresponds to the AMPA-insensitive, QUIS-sensitive, [3H]glutamate binding reported by Cha et al .…”
Section: Fig 2 Effect Of Anions On 1s3r-acpdsupporting
confidence: 58%
“…Our studies identified ECL2 as being necessary for relaying the agonist-induced conformational changes to the 7TM domain by providing a second, rigid attachment point between the ECD and transmembrane domains. Thus, we propose that the ECL2-CRD interaction is the structural basis for the allostery that has been observed between the ECD and 7TM domains 36,37 . While our results do not fully explain how agonist binding at the VFT leads to G protein coupling and activation, they do support a model in which both inter- and intrasubunit rearrangements are required for full activity 5 .…”
Section: Discussionmentioning
confidence: 77%
“…The radioligand binding paradigm was characterized by initially determining the equilibrium binding time for [ 3 H]glutamate and performing a saturation analysis that described a K d for [ 3 H]glutamate in this preparation that was consistent with previous studies (Baudry and Lynch, 1981;Cross et al, 1986;Oillet et al, 1995). Because we were interested in the potential interactions of acamprosate at all glutamate binding sites, we chose not to add saturating concentrations of NMDA and ␣-amino-3-hydroxy-5methyl-4-isoxazolepropionic acid in the binding studies as done by others to isolate mGluRs (Catania et al, 1994;Martín et al, 1993;Schoepp and True, 1992;Wright et al, 1994). The displacement of [ 3 H]glutamate by 1 mM unlabeled glutamate also provided a reference for comparison across all competition studies.…”
Section: Discussionmentioning
confidence: 87%
“…The interaction of acamprosate at these sites is also differentially altered in the presence of 100 M GTP as compared with the two agonists unlabeled glutamate and trans-ACPD. GTP produces a transition of mGluRs from high-to low-affinity states (Martín et al, 1993). This transition affects the ability of micromolar concentrations of Na-acamprosate to displace [ 3 H]glutamate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation